Allergic FcεRI‐ and pseudo‐allergic MRGPRX2‐triggered mast cell activation routes are independent and inversely regulated by SCF. Issue 1 (20th September 2017) - Babina, M.; Guhl, S.; Artuc, M.; Zuberbier, T.
Abstract: While allergic mast cell (MC) degranulation occurs by FcεRI aggregation and varies in strength among subjects, the analogous pseudo‐allergic route was recently uncovered to proceed via MRGPRX2. Here, we examine interindividual variability in skin MC responses to FcεRI triggering vs those evoked by MRGPRX2. While population‐based variability is comparable between the routes, FcεRI‐ and MRGPRX2‐stimulated pathways are completely independent from each other, and responsiveness to one has therefore no predictive value for the other. Conversely, degranulation triggered by compound 48/80 is highly correlated to the process elicited by substance P. MRGPRX2 mRNA shows pronounced population‐based variability (coefficient of variation 102.9%). Surprisingly, stem cell factor (SCF) as the MC‐supportive mediator par excellence potently inhibits pseudo‐allergic degranulation, while it simultaneously promotes allergic stimulation via FcεRI. We conclude that SCF can have selective MC‐dampening functions. Clinically, the data imply that subjects highly reactive in one pathway are not automatically hyper‐responsive in terms of the alternative route.